Design of multiple input multiple output patch antenna for multiband applications - Abdulrab, Waheeb Salim; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Ahmed, Musse Mohamud (IEEE, 2016)
Multiple Input Multiple Output (2x2MIMO) patch antenna for multiband applications has been proposed in this paper. The proposed design has reduced the mutual coupling and enhance the bandwidth and efficiency. The proposed 2x2 MIMO patch antenna is simulated using Computer Simulation Technology (CST) . The isolation ,bandwidth and efficiency are enhanced by using groups of rings around the stepped cut at four corner and mid slot separation on the radiating path of the antenna. The bandwidth 1.4 GHz to 2.5 GHz, and 3GHz to 5.5 GHz are achieved. The rings used in this design are essential for having more new resonant frequencies. A novel concept of mid space separation on the patch is used to improve the isolation. Coupling coefficients of the simulated proposed antenna is found lower than -10dB for all the desired frequencies(1.5GHZ, 1.8GHz, 2.4GHz, 3.5GHz,5.2GHz and 5.5 GHz. 9.99 dB Diversity gain of the proposed 2x2 MIMO antenna system is also achieved higher. Envelope correlation coefficient (ECC) is less than 0.007 at the desired frequency bands . This results implies that the proposed antenna system is suitable for MIMO applications. Radiation efficiencies are achieved above 70% for all desired frequencies . Hence the final design of 2x2 MIMO patch antenna can be used for GSM(1.5GHz), LTE (1.8GHz),WiFi (2.4GHz), and WiMax (3.5GHz, 5.2 GHz and 5.5 GHz) applications. Keywords -Multiple Input Multiple Output (MIMO), Envelope correlation coefficient ( ECC),Single Input Single Output(SISO) , Rectangular Microstrip Patch Antenna (RMPA).